Listening comprehension success among EFL preschool children using internet-based materials - Kamal Heidari Soureshjani,; Neda Etemadi, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2012)
The current study investigated the impact of computer-based stories on the comprehension of oral English by a group of Iranian EFL school children. To achieve the intended purpose, a quasi-experimental research study was carried out in a one of Iranian pre-schools in Shahrekord, Iran. A pre-test and a post-test were then used to ascertain whether internet-based stories could improve listening comprehension in English as a Foreign Language. Results revealed that the experimental group outperformed the control group in the final test administered. The findings broached interesting subjects related to the use of technology in the context of foreign language learning. Studies like this can contribute significantly to the more effective use of technology in order to improve the learning process quality.